2004
DOI: 10.1007/s11214-004-1434-0
|View full text |Cite
|
Sign up to set email alerts
|

The Cassini Radio and Plasma Wave Investigation

Abstract: The Cassini radio and plasma wave investigation is designed to study radio emissions, plasma waves, thermal plasma, and dust in the vicinity of Saturn. Three nearly orthogonal electric field antennas are used to detect electric fields over a frequency range from 1 Hz to 16 MHz, and three orthogonal search coil magnetic antennas are used to detect magnetic fields over a frequency range from 1 Hz to 12 kHz. A Langmuir probe is used to measure the electron density and temperature. Signals from the electric and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
384
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 475 publications
(398 citation statements)
references
References 89 publications
4
384
0
Order By: Relevance
“…The analysis uses the integrated intensity of the radio waves (integration over 10 min in time and over 80-500 kHz in frequency for SKR, and 3-8 kHz for the narrowband emissions) as measured by the Cassini Radio and Plasma Wave Science (RPWS) instrument (Gurnett et al, 2004). The integrated intensity is distance-normalized by dividing by the average intensity over one Saturn rotation.…”
Section: Skr and Narrowband Radio Emission Modulation Spectrogramsmentioning
confidence: 99%
“…The analysis uses the integrated intensity of the radio waves (integration over 10 min in time and over 80-500 kHz in frequency for SKR, and 3-8 kHz for the narrowband emissions) as measured by the Cassini Radio and Plasma Wave Science (RPWS) instrument (Gurnett et al, 2004). The integrated intensity is distance-normalized by dividing by the average intensity over one Saturn rotation.…”
Section: Skr and Narrowband Radio Emission Modulation Spectrogramsmentioning
confidence: 99%
“…In such a case the base impedances have to be taken into account. This can change the results significantly, in particular near the resonance frequencies, as Gurnett et al (2004), Macher et al (2007) and Bale et al (2008) have already shown in the context of former spaceborne antennas.…”
Section: Effective Area Patternmentioning
confidence: 89%
“…Data was analysed mainly from the magnetometer and use the plasma instruments, the Radio and Plasma Wave Science (RPWS) [Gurnett et al, 2004] and the Ion Mass Spectrometer (CAPS-IMS) [Young et al, 2004]. Since the focal point of this study is a much smaller sample size of crossings, the Mach numbers …”
Section: Methodsmentioning
confidence: 99%
“…Figure 3.1 shows where each of the twelve instruments are located on the spacecraft. The data presented and interpreted in these studies are principally from Cassini's Fluxgate Magnetometer (MAG) [Dougherty et al, 2004] with supporting data from the Radio and Plasma Wave Science (RPWS) [Gurnett et al, 2004] and Ion Mass Spectrometer (IMS) [Young et al, 2004]. In this chapter, we will begin with a brief overview of the mission and then describe the instruments used.…”
Section: Spacecraft and Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation